Multi‐angular ground‐based SAR system for soil surface roughness characterisation. Issue 15 (9th July 2015) - Wang, H.Q.; Méric, S.; Allain, S.; Pottier, E.
Abstract : A ground‐based (GB) synthetic aperture radar (SAR) system is proposed for soil surface roughness discrimination at the C‐band. By using this GB‐SAR system, the multi‐angular SAR measurement is realised at different resolution cell sizes. The specific levels of surface roughness are set deliberately to analyse the roughness contribution on the multi‐angular SAR signature in a controlled experimental condition. Based on the GB‐SAR measurement, the effect of incidence angle on SAR sensitivity is studied under two resolution cell sizes for retrieving soil surface roughness. The results show that, the using the GB‐SAR system, the high incidence angle configuration (e.g. > 40°) is optimal to discriminate surface roughness, which is more significant at small resolution cell sizes (e.g. 30 cm). This study indicates the effectivity of the GB‐SAR system to validate the SAR backscattering mechanisms.